Blended Learning in TVET: Bridging Adult Learning - Wiediartini,Denny Dermawan (International Conference on Industrial Revolution for Polytechnic Education, 2020)
The Fourth Industrial Revolution is a challenge for TVET and should become an integral part of the TVET Strategy. There should be shifting learning environment in TVET to anticipate the trend of the changing of the technology and the essential of adult learner. Technology mediated interactions between students, instructor, and learning resources are needed to accommodate unique characteristics of adult learner. Blended Learning courses combine e-learning and face-to-face learning activities to improve student-learning outcomes and to address important institutional issues. The purpose of this paper is to discuss the strategy of implementation of blended learning. Blended learning in meaningful ways if there is a clear and supportive institutional strategy. This article categories three strategy to implement blended learning, from the instructor, student and organization view.